Determinação simultânea de cobalto e níquel - Antunes,Patrícia Alexandra (1998)
The simultaneous determination of cobalt and nickel is a classical analytical problem. A great number of reagents associated with several techniques of analysis have been applied to achieve this determination. In this review 117 references, which appeared between 1996-1980, are described and classified according to the technique applied.